Increased Cerebrospinal Fluid Levels of Soluble Triggering Receptor Expressed on Myeloid Cells 2 and Chitinase-3-Like Protein 1 in Idiopathic Normal-Pressure Hydrocephalus - Yang, Fuxia; Yang, Lu; Fang, Xuhao; Deng, Yao; Mao, Renling; Yan, Aijuan; Wei, Wenshi (Journal of Alzheimer's disease, 2023)
Background: Neurodegenerative disease pathology is associated with neuroinflammation, but evidence on idiopathic normal pressure hydrocephalus (iNPH) remains limited and cerebrospinal fluid (CSF) biomarker profiles need to be elucidated. Objective: To investigate whether iNPH pathological mechanisms are associated with greater CSF markers of core Alzheimer’s disease pathology (amyloid-β42 (Aβ42), phosphorylated tau (P-tau)), neurodegeneration (total tau (T-tau)), and neuroinflammation (soluble triggering receptor expressed on myeloid cells 2 (sTREM2), chitinase-3-like protein 1 (YKL-40)). Methods: The study analyzed lumbar CSF samples from 63 patients with iNPH and 20 age-matched orthopedic surgery patients who had no preoperative gait or cognitive impairment (control group). Aβ42, T-tau, P-tau, sTREM2, and YKL-40 in different subgroups were investigated. Results: CSF sTREM2 levels were significantly higher in the iNPH group than in the control group, but no significant between-group difference was noted in YKL-40. Moreover, YKL-40 levels were significantly higher in the tap test non-responders than in the tap test responders (p = 0.021). At the 1-year follow-up after shunt surgery, the CSF P-tau levels were significantly lower (p = 0.020) in those with gait improvement and the CSF sTREM2 levels were significantly lower (p = 0.041) in those with cognitive improvement. In subgroup analysis, CSF sTREM2 levels were strongly correlated with CSF YKL-40 in the iNPH group (r = 0.443, p < 0.001), especially in the tap test non-responders (r = 0.653, p = 0.002). Conclusion: YKL-40 and sTREM2 are disease-specific markers of neuroinflammation, showing higher CSF levels in iNPH. In addition, sTREM2 is positively associated with YKL-40, indicating that interactions of glial cells play an important role in iNPH pathogenesis.